In vitro regeneration of eight cultivars of Brassica oleracea var. capitata - Gerszberg, Aneta (In Vitro Cell Dev Biol Plant, 2014)
Eight cultivars of Brassica oleracea var. capitata and two types of explant (hypocotyl and cotyledon) were tested for their potential to regenerate under in vitro conditions. Hypocotyl and cotyledon explants from 10-d-old seedlings were subcultured onto different callus induction media based on Murashige and Skoog (MS) basal medium supplemented with 1% sucrose and different concentrations and combinations of plant growth regulators. Hypocotyl explants were found to be more suitable for callus induction and organogenesis than cotyledon explants for all cultivars tested. In terms of regeneration, the cv. ‘Amager’ was significantly more responsive than the other cultivars tested and produced the highest number of shoots/buds per explant. Moreover, among five types of media tested, MS + 8.88 μM 6-benzyloaminopurine (BAP) + 0.53 μM α-naphthylacetic acid (NAA) was most effective for shoot regeneration. Rooting was achieved within 10–15 d on all the rooting media, but MS medium containing 5.37 μM NAA produced the maximum number of strong and healthy roots. Plantlets (95%) were subsequently established in the greenhouse, and no phenotypic variations were observed among regenerated plants. This plant regeneration protocol could be suitable for a wide range of cabbage cultivars.